Effect of Biological Relatedness on Perfume Selection for Others: Preliminary Evidence. (March 2017) - Sobotková, Markéta; Fialová, Jitka; Roberts, S. Craig; Havlíček, Jan
People tend to choose perfumes to complement their body odour. As kin share some body odour qualities, their ability to select complementary perfumes for relatives might be higher compared with selection for nonrelatives. We tested this in two studies, comparing selection of a perfume for a target man by himself and by either a familiar but unrelated individual (girlfriend; Study 1) or a relative (sister; Study 2). Target men applied the two perfumes (own or other's choice) to their axillae and then wore cotton pads for 12 hr. Collected perfume-body odour blends and perfumes alone were assessed by rater panels. In Study 1, the blends were rated as nominally more pleasant when body odours were mixed with the perfumes selected by girlfriends compared with those selected by target men themselves. In Study 2, body odours mixed with perfumes selected by sisters were rated significantly more attractive than those mixed with perfumes selected by target men. No significant differences were found for attractiveness and pleasantness ratings when perfumes were rated alone, suggesting that it was the resulting blends that were uniquely different. Our results indicate that sisters might be particularly tuned to select suitable perfumes for their siblings.